Uma investigação (Nano)sintático-semântica das preposições espaciais do português brasileiro - Ferreira, Thayse Letícia (Universidade Federal de São Carlos, 2021)
Spatial prepositions have been one of the greatest puzzles in linguistics in the the past few decades. In this thesis, we contribute to the understanding of this class, by investigating place (`em'/`in', `entre'/`between') and path (`de'/`from', `desde'/`starting from', `por'/`by', `a'/`to', `para'/`towards', `até'/`up to') prepositions in Brazilian Portuguese (BP), along with the so-called complex prepositional phrases, such as `in front of'. Within the theoretical framework of Nanosyntax and Formal Semantics, we explore an articulated hierarchy of features for the spatial domain, associated with the class of prepositions, as well as we provide for each of these terminals a semantic interpretation in terms of a lambda calculus. This thesis seeks, in the Montaguian spirit, to investigate spatial prepositions in an interpretable formal(syntactic) system. In this framework, then, we suggest, at the theoretical level, that spatial prepositions select as their internal argument a spatial entity of an abstract level, referring to a kind. Given that the preposition's internal argument, named GROUND (Talmy, 2000), denotes a spatial kind, this element requires an instantiation, that has to be given by a predicate capable of providing an exemplar of the kind, role assigned precisely to spatial prepositions across languages. Hence, we discuss the nature of the preposition's internal argument and revisit the role of the spatial preposition in natural languages, which becomes a kind-level predicate and can't be seen anymore just as a relational predicate between any type of entity. Assuming, then, that there are spatial entities in our ontology that can be manipulated by specific predicates, we propose that these entities are created by a syntactic head called Region [Reg], initially suggested by Romeu (2014). [Reg] is in our proposal a free access operator, responsible for taking an entity with reference in the individual domain, of type , and converting this entity into the space that the individual occupies, its region, of type . The spatial preposition, next, through [LocP [PP]], selects and instantiates the spatial argument, making it compatible with the subsequent derivation. Still at the theoretical level, we suggest that the axial part terminal [AxPart], suggested by Svenonius (2006), cannot be an independent element in the syntax, since all the arguments raised by the author to defend its functional nature in fact only prove their kinship with the noun class. Thus, the notion of axiality involved in prepositional phrases such as `in front of' can be seen as part of the concept associated with each lexical item. Along these lines, `front' can be analyzed as a relational noun, which allows us to create spatial entities in the same way from simple names, like `house', and complex ones, like `front of house'. At the empirical level, we analyze cases of syncretism and competition between BP prepositions, thus seeking an individuation of each item in terms of fine-grained properties. We observe that for locative PPs there is not much in the formal structure that governs their behavior, this class is mainly restricted by the concept, which separates `in' as a non-projective preposition from `between' and phrases such as `in front of', `next to', among others, classified as projective. Path prepositions' behavior is not governed by the concept, but by terminals of the functional sequence, in such a way that the Bound head systematically blocks the cases of possible syncretisms in the class, preventing the building of sentences such as ``*Ana left/is since home'', with a locative reading. When exploring a formal model to the grammar architecture, we are able to observe, then, that the behavior of spatial prepositions depends not only on the computation features, but also on our world's knowledge, via the notion of concept.
A (Nano)syntactic-semantic investigation of Brazilian Portuguese spatial prepositions
Keywords: Preposições espaciais; Nanossintaxe; Semântica Formal; Hierarquia espacial; Spatial Prepositions; Nanosyntax; Formal Semantics; Spatial Hierarchy; LINGUISTICA, LETRAS E ARTES::LINGUISTICA; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::TEORIA E ANALISE LINGUISTICA